Rapport om en rapport: Tychsens origineller Bericht über die Mecklenburischen Juden von 1769 - Rohlén-Wohlgemuth, Hilde (Nordisk judaistik/Scandinavian Jewish Studies, 1990)
This report comments on a report by O.G. Tychsen, who was a professor in Rostock and specialized in orientalism and Hebrew language. He had frequent contact and correspondence with Jews, but sometimes his descriptions of them were of sharp character. Tychsen wrote his report on Jews in Mecklenburg in 1769.